The Impacts of Social Media and Work-Life Balance: A Systematic Literature Review of Recent Evidence. - Mat, Khalid Amin; Mohd Zani, Amirudin; Abdullah, Nasiha; Adenan, Nur Dalila (Journal of Islamic, Social, Economics and Development, 2025)
This systematic literature review (SLR) investigates the impacts of social media usage on work-life balance (WLB) in contemporary workplace settings, with a particular focus on studies conducted between 2020 and 2025. Drawing on 17 peer-reviewed empirical studies, the review explores how social media influences employees’ ability to manage boundaries between work and personal life. The studies analyzed employed diverse methodologies, including cross-sectional surveys, qualitative interviews, and structural equation modeling. Key findings reveal that while social media can enhance communication, collaboration, and recovery during work breaks—thereby supporting WLB—it can also contribute to technostress, burnout, and blurred boundaries when used excessively or compulsively. Psychological constructs such as fear of missing out (FoMO), social media communication self-efficacy, and phubbing emerged as critical mediators and moderators. The review highlights the dual nature of social media as both a facilitator and disruptor of WLB, depending on usage patterns, platform type, and individual or organizational context. It concludes that a balanced and mindful approach to social media use, supported by digital well-being policies and boundary management strategies, is essential for optimizing its benefits while minimizing its risks. These insights offer valuable guidance for researchers, practitioners, and policymakers aiming to foster healthier and more sustainable work-life integration in the digital age.